Between hypoxia or hyperoxia: not perfect but more physiologic - Robba, Chiara; Ball, Lorenzo; Pelosi, Paolo (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
The main goal of mechanical ventilation in patients with acute distress respiratory syndrome (ARDS) is to provide an adequate oxygenation, and respiratory support and supplemental oxygen are necessary measures in most patients (1). It has been previously reported that, among ARDS survivors, the prolonged exposure to even moderate hypoxemia can determine neurological complications and cognitive disfunction (2). Supplemental oxygen is also part of the acute management of different critical conditions including cardiac arrest and circulatory shock, in order to compensate the imbalance between oxygen supply and requirements (3).